Immunomodulating role of the JAKs inhibitor tofacitinib in a mouse model of bleomycin-induced scleroderma. Issue 3 (March 2021) - Aung, Wah Wah; Wang, Chenyang; Xibei, Jia; Horii, Motoki; Mizumaki, Kie; Kano, Miyu; Okamura, Ai; Kobayashi, Tadahiro; Matsushita, Takashi
Highlights: Tofacitinib attenuates scleroderma in a mouse model by reducing fibrosis in the skin and lungs. Tofacitinib lowers collagen production, and the mRNA expression of collagen and fibrogenic cytokines. Tofacitinib reduces adaptive immune response by affecting cytokine-producing T cells and T-helper/T-regulatory balance. Tofacitinib restores cytokine-producing effector and regulatory B cells balance. Tofacitinib diminishes infiltration of macrophages in the skin and lung tissues. Abstract: Background: Janus kinase (JAK)-signal transducer and activator of transcription (STAT) was hyperactivated in biopsies from patients with systemic sclerosis (SSc) and in several autoimmune disease models. Tofacitinib, a pan-JAK inhibitor, blocks the downstream signaling of multiple cytokines and has exhibited therapeutic efficacy in various autoimmune diseases, although its immunomodulating property in scleroderma is unclear. Objective: To evaluate the effect of tofacitinib on the modulation of cytokine-producing T and B cells, and proinflammatory cells in a mouse model of SSc. Methods: Bleomycin (BLM)-induced SSc was generated by intradermal injection of BLM or PBS for control. Mice received intraperitoneal tofacitinib (20 mg/kg) or vehicle 3 times per week from day 0–28. Mice were sacrificed at day 28 after the last BLM/PBS injection. Results: Tofacitinib administration significantly alleviated fibrosis of the skin and lungs in scleroderma mouse model. Furthermore, tofacitinib suppressed adaptive and innate immune responses by reducing splenocytes, total lymphocytes, CD4 + T helper cells (especially Th2 and Th17 subtypes), IL-6-producing effector B cells, PDCA-1 + dendritic cells in the spleen, and infiltration of F4/80 +, CD206 + and CD163 + macrophages in the skin and lungs. Conversely, tofacitinib increased the proportions of splenic regulatory T and B cells. The mRNA expression of extracellular matrix proteins and fibrogenic cytokines was downregulated by tofacitinib in both the skin and lungs. Conclusion: These observations suggest JAK inhibition as a therapeutic approach for the treatment of inflammatory and fibrotic diseases, and highlight the potential of tofacitinib as a promising candidate for treating patients with scleroderma.